Unprecedented extinction of tree species by fungal disease. (September 2021) - Fensham, Roderick J.; Radford-Smith, Julian
Abstract: Myrtle rust is caused by the fungus Austropuccinia psidii and impacts some species in the extremely large and mostly Gondwanic plant family, the Myrtaceae. Given the location of its wild relatives, the fungal pathogen originated in South America and spread rapidly across the Pacific. Here we report on extensive surveys from Australian rainforest to predict a plant extinction event of unprecedented magnitude. The results predict the imminent extinction of 16 rainforest tree species in the wild due to myrtle rust within a generation. A further 20 species may be at risk, but further monitoring is required to determine their fate. Myrtle rust retards growth and precludes reproduction on these severely affected species. To avoid total extinction, strategies for in-situ and ex-situ rescue are presented.